Sero-prevalence and Perception of Brucellosis among High-Risk Groups, A Cross-sectional Study - Bushara, Mohamed Osman Elamin (Journal of Liaquat University of Medical & Health Sciences, 2023)
Objective: To determine the seroprevalence of Brucellosis and assess the disease’s perception among high-risk groups. Methodology: This descriptive cross-sectional, community-based study was conducted among 125 high-risk group individuals vulnerable to infection with Brucellosis and compared to 50 individuals of non-risk groups. Obtained sera were tested for the presence of antibodies to Brucella using the Rose Bengal plate test and standard tube agglutination test. A questionnaire was designed to assess the risk behavior and previous knowledge about the disease. Results: The males were 78%, and the females were 22%. The seropositivity of Brucellosis was 3.2% among people at high risk and nil for the non-risk groups. The disease was prevalent in dairy farmers, which was more prevalent in dairy farmers (2.4%) and slaughterhouse workers (0.8%). All infected persons were males; the disease is most common in the age group 15-25 years. Conclusion: There was a statistically significant correlation between education level and the prevalence of Brucellosis. The two laboratory methods used to diagnose Brucellosis gave the same results. Routine checkups and education of at-risk individuals are recommended to help control the disease.